Prilaku Subgrade Pada Studi Kasus Tebal Perkerasan yang di Subtitusi Menggunakan Semen - Yandriguna, Medi; Iswan, Iswan; Zakaria, Ahmad (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2018)
In the field of highway damage to road pavement in addition to weather factors and overloading can also occur due to poor subgrade. A good alternative so that the soil on the highway subgrade does not experience excessive swelling is to use cement additives.Soil samples were tested using subgrade soil material originating from the RA. Basyid passageway of Fajar Baru Village, Jati Agung Subdistrict, South Lampung at STA 3 + 900 and variations of cement used were 0, 4, 8 and 12%. The test carried out is by testing the swelling of soil against CBR which has been marred for 3 days, then based on the results of the test, the calculation of pavement thickness was carried out by the method of analysis of components of SKBI 2.3.26.1987.In testing physical properties, the soil includes the classification of A-6 soil or poorly categorized soil types. However, after adding variations in soil classification cement into a good A-2-4 category. In the CBR swelling test on 0% cement percentage swelling values were 0.62% and CBR 0.9%, in the 4% percentage swelling value 0.27% and CBR 42.6%, at the percentage of 8% swelling value 0.19% and CBR 53.2%, and 12% percentage swelling value 0.06% and CBR 78.1%. From the calculation of the pavement thickness, the greater the CBR value, the thicker the thickness of each layer.Keywords: CBR, Soil Swelling, Pavement Thickness, Stabilization, Cement